1948
DOI: 10.1071/ch9480213
|View full text |Cite
|
Sign up to set email alerts
|

Equilibria in Furfural-Water Systems under Increased Pressure and the Influence of Added Salts upon the Mutual Solubilities of Furfuraland Water

Abstract: Liquid-vapour equilibrium data are reported for the furfural-water system a t pressures of 6.17, 7.85, and 9.83 kg. per cm.V Under these pressures the system forms a homoazeotropic mixture differing only slightly in composition from the heteroazeotropic mixture formed at normal pressures. The data are checked by the calculation of activity coefficients. Abnormal activity coefficients are found for water in mixtures of high furfural content.The equation 2209 log,, P = ---L7.959

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Finally, the paper published by Curtis and Hatt in 1948 needs to be included in this discussion. 83 The main added value of this paper is the liquid-vapor equilibrium data presented in the first two parts. However, in the last part, the reaction rates of loss reactions of furfural in pure water and in sulphuric acid solutions are presented.…”
Section: Furfural Loss Reactionsmentioning
confidence: 99%
“…Finally, the paper published by Curtis and Hatt in 1948 needs to be included in this discussion. 83 The main added value of this paper is the liquid-vapor equilibrium data presented in the first two parts. However, in the last part, the reaction rates of loss reactions of furfural in pure water and in sulphuric acid solutions are presented.…”
Section: Furfural Loss Reactionsmentioning
confidence: 99%
“…The vapor-liquid equilibrium behavior of water-furfural is such that an azeotrope is formed, also at higher pressures (Curtis and Hatt 1948). Figure 9 depicts this two phase behavior (Zeitsch 2000) for the part in which the vapor phase is enriched in furfural.…”
Section: Mtc Processmentioning
confidence: 99%
“…Microsoft Excel is used for early VLE modeling and quantitative calculation of the model's suitability, while MATLAB R2021a is used for curve visualization of the modeling. In this study, the UNIQUAC model will be applied on a furfural and water mixture distillation data by [10] at 6.17 kg/cm 2 or 4,538.4 mmHg pressure. The UNIQUAC equation for VLE will be as follows.…”
Section: Methodsmentioning
confidence: 99%
“…There are only several research that observed VLE models on furfural and water mixtures. This study was conducted to develop a VLE curve from the distillation data of [10] study with the UNIQUAC model. The distillation data from Curtis and Hatt has been tested with the van Laar model, which is why UNIQUAC is chosen to prove that other models can be used to simulate the VLE curve.…”
Section: Introductionmentioning
confidence: 99%